ABUSE OF PSYCHOACTIVE SUBSTANCES BY YOUNG PEOPLE AGED 15-24 IN SERBIA - Milicevic, Tanja; Marinkovic, Ana; Radovanovic, Snezana; Gracic, Danijela; Krulj, Sanja; Milosavljevic, Jasna; Gazdic, Mirjana; Simovic Siljkovic, Divna; Mujkovic, Marija; Radivojevic, Sladjana; Stanojlovic, Predrag (HEALTH CARE, 2021)
Introduction/Aim: The abuse of psychoactive substances among young people is a significant global public health problem. The aim of the study was to examine the prevalence of psychoactive substances use among adolescents in Republic of Serbia.Methods: In this secondary analysis of data, we used data from the Serbian national survey of population health from 2013, which was conducted by the Ministry of Health of the Republic of Serbia and Institute of Public Health of Serbia. This cross-sectional study, which was conducted on a representative sample of the population of Serbia, included 1722 respondents aged 15 to 24 years (49% of women and 51% of men).Results: Out of the total number of young people aged 15-24, ⅓ of them declared themselves on the issue of cigarette consumption in the following way: 52.1% consumed cigarettes daily and 20.8% occasionally. Among the respondents, 41.3% were exposed to the indoor tobacco smoke for 1 hour or more daily, while 49.4% were concerned about the harmful effects of smoking on their health. Only a third said that they had never consumed alcohol or had only taken a few sips of alcohol in their lifetime. Men smoked slightly more often (52.2%) and consumed alcohol more often (every day or almost every day 0.7%, 5-6 days a week 0.7%, 3-4 days a week 4.5%, 1- 2 days a week 15.7%, as well as 2-3 days a month 16.8%) than women (0.3%; 0.2%; 1.7%; 7.8%; 12%). About ¼ adolescents used 6 or more alcoholic beverages 1-3 days a month for the last 12 months. During the last 12 months, the respondents most often consumed painkillers (20.2%), sedatives (1.7%) and sleeping aids (2.3%) on their own initiative. There were 0.7% of users of illicit psychoactive substances (cannabis, cocaine, and glue). Conclusion: The results of the study of psychoactive substances abuse among young people in Serbia point to the necessity to work on the prevention of risky behavior.
Keywords: addiction to psychoactive substances, cigarettes, alcohol, painkillers, sedatives, sleeping aids, young people, population survey